Short Communication: The color fastness of cotton cloth dyed with dye extracted from skin of shallot (Allium ascalonicum) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sarwono, Santosa S, Prameswari NS. 2019. Short Communication: The color fastness of cotton cloth dyed with dye extracted from skin of shallot (Allium ascalonicum). Biodiversitas 20: 2475-2479. Inventing new sources of materials in textile coloration industry in Indonesia, especially batik industry, is necessary for the preservation of Indonesia’s textile heritage. Focusing on the exploitation of Allium ascalonicum L., this present study aimed at discovering whether shallot skin can be used as a natural dye for textile through the fixation of alum, chalk, and tunjung. It also tried to shed light on the method of applying dye from the skin of shallot to cotton cloth for batik and measured the color fastness. The test of color fastness was done using Staining Scale and Grey Scale. Data were gathered through observation and analyzed descriptively. The results of color fastness test showed that the color fastness of cotton cloth dyed with extract of shallot skin using alum fixation was fairly good based on color change and sufficient based on staining scale. The test results using chalk fixation showed that the color fastness was poor based on color change, but sufficient based on staining scale. Other results with tunjung fixation showed that the color fastness was sufficient.
Keywords: Batik, natural dye, shallot skin, textile